Association between obesity and likelihood of remission or low disease activity status in psoriatic arthritis applying index-based and patient-based definitions of remission: a cross-sectional study - Laure Gossec; Ana-Maria Orbai; Josef S Smolen; Juan D Cañete; Maarten de Wit; Laura C Coates; Uta Kiltz; Penelope Palominos; Rossana Scrivo; Andra Balanescu; Martin Soubrier; Lihi Eder; et al. (RMD Open, 2023)
Objectives We aimed to evaluate whether obese patients with psoriatic arthritis (PsA) were less likely to be in remission/low disease activity (LDA).Methods We used data from the ReFlaP, an international multi-centre cohort study (NCT03119805), which recruited consecutive adults with definite PsA (disease duration ≥ 2 years) from 14 countries. Demographics, clinical data, comorbidities, and patient-reported outcomes were collected. Remission/LDA was defined as Very Low Disease Activity (VLDA)/minimal disease activity (MDA), Disease Activity in PSoriatic Arthritis (DAPSA) ≤4/≤14, or by patients’ opinion. Obesity was defined as physician-reported and/or body mass index ≥30 kg/m2. We evaluated the association between obesity and the presence of remission/LDA, with adjustment in multivariable regression models.Results Among 431 patients (49.3% women), 136 (31.6%) were obese. Obese versus non-obese patients were older, more frequently women, had higher tender joint and enthesitis counts and worse pain, physical function and health-related quality of life. Obese patients were less likely to be in VLDA; DAPSA remission and MDA, with adjusted ORs of 0.31 (95% CI 0.13 to 0.77); 0.39 (95% CI 0.19 to 0.80) and 0.61 (95% CI 0.38 to 0.99), respectively. Rates of DAPSA-LDA and patient-reported remission/LDA were similar for obese and non-obese patients.Conclusion PsA patients with comorbid obesity were 2.5–3 folds less likely to be in remission/LDA by composite scores compared with non-obese patients; however, remission/LDA rates were similar based on the patients’ opinion. PsA patients with comorbid obesity may have different disease profiles and require individualised management.